UMP InECCE discusses issues on alternative energy - UMP, PNC
Universiti Malaysia Pahang (UMP)'s Faculty of Electrical & Electronics Engineering (FKEE) held its first Electrical, Control and Computer Engineering International Conference (InECCE 2011) for two days beginning June 21, 2011 at Hyatt Regency Kuantan Resort Hotel.